Design, synthesis and cytotoxic effects of curcuminoids on HeLa, K562, MCF-7 and MDA-MB-231 cancer cell lines - Zamrus, Siti Noor Hajar; Akhtar, Muhammad Nadeem; Yeap, Swee Keong; Quah, Ching Kheng; Loh, Wan-Sin; Mohammed Alitheen, Noorjahan Banu; Zareen, Seema; Tajuddin, Saiful Nizam; Hussin, Yazmin; Ali Shah, Syed Adnan (SpringerOpen, 2018)
Background Curcumin is one of the leading compound extracted from the dry powder of Curcuma longa (Zingiberaceae family), which possess several pharmacological properties. However, in vivo administration exhibited limited applications in cancer therapies.